Uso de bioindicadores para monitorar diferentes usos e ocupações de solos e a qualidade das águas do rio Chopim, da unidade de conservação "Refúgio de Vida Silvestre dos Campos de Palmas" e seu entorno - Schütz, Daiana Lauxen (2020)
The Wildlife Refuge of Campos de Palmas (RVS-CP) is an Integral Protection Conservation Unit (UC), formed by private properties, where activities such as agriculture and forestry are developed. This UC houses springs of the Chopim River hydrographic basin, an important source of water supply in the region. Thus, the objective of the present study was to use the bioindicators Allium cepa L., for the cytotoxicity and mutagenicity test, and Eisenia fetida, for the leakage test, to assess the quality of the waters of the Chopim River and the different uses and occupations of the soils of the RVS-CP and its surroundings, during the four seasons of a year. Rio's water samples were collected at five points: Point 1 (source), Points 2 to 4 (within the RVS-CP) and Point 5 (immediately outside the RVS-CP). The soil samples were collected in forestry, agriculture and field areas (within the RVS-CP) and agriculture outside the RVSCP. Regarding the water samples from the Chopim River, the data showed that all collection points had a cytotoxic effect for the bioindicator A. cepa, in at least one season of the year. These results may be due to the inadequate management of the areas surrounding the collection points, such as: forestry, native fields, pastures, agriculture and the presence of housing. For the animal bioindicator (earthworm), only Points 1 (winter) and 5 (autumn) were toxic. As for mutagenicity, Points 1 and 4 (spring), 1 and 2 (summer) and 3 (autumn) showed a mutagenic effect for the meristematic cells of A. cepa, indicating that this effect was only observed in points within the RVS-CP. In addition, for the plant bioindicator, the rainiest seasons (spring and summer) were those that showed the most evident cytotoxic and mutagenic effects. For soil samples, the uses for silviculture (spring) and field (summer) showed a cytotoxic effect for A. cepa and, the use for agriculture outside the UC (spring) had a stimulating effect of cell divisions and mutagenic for this vegetable bioindicator. For E. fetida, land uses for agriculture within the RVS-CP (winter), field (autumn and spring), forestry (autumn and spring) and agriculture outside the UC (spring) have leakage rates above 60% and, thus, toxic effect. These results can be justified by the presence of macronutrients in the different uses and occupations of the soil evaluated, especially calcium, phosphorus, magnesium, sodium and potassium and, of metals, such as aluminum, titanium, vanadium, iron, nickel, lead, manganese, barium and chromium. Thus, the results of the present study highlight the importance of using different organisms to monitor environmental quality and indicate the need to implement preventive and educational measures in the RVS-CP, to avoid the toxic, cytotoxic and mutagenic effects found and guarantee the integrity of this UC and the active protection of the environment and biodiversity.